PENGARUH MODEL PEMBELAJARAN INDEX CARD MATCH MELALUI MISSING HIJAIYAH TERHADAP KEMAMPUAN MENGENAL HURUF HIJAIYAH PADA ANAK USIA 5-6 TAHUN - Windiana Windiana; Syamsuardi Syamsuardi; Muhammad Yusri Bachtiar (Lembaga Penerbitan dan Publikasi Ilmiah (LPPI) Universitas Muhamamdiyah Palopo, 2023)
This research is a quasi-experimental research with the aim of knowing the effect of the index card match learning model through missing hijaiyah on the ability to recognize hijaiyah letters before and after being treated to children aged 5-6 years in Bontotiro District, and aims to find out whether there is influence from the learning model index card match through missing hijaiyah on the ability to recognize hijaiyah letters in children aged 5-6 years in Bontotiro District. The independent variable in this study is the index card match learning model through missing hijaiyah, then the dependent variable is the ability to recognize hijaiyah letters. The population of this study is 90 children aged 5-6 years in Bontotiro District. then for the technique used for sampling in this study using purposive sampling consisting of 40 children which were divided into an experimental group with a total of 20 children and a control group of 20 children. Descriptive statistical analysis techniques and parametric analysis are data analysis techniques used in this study. Data analysis shows Asym (2 tailed) = 0.009 <0.05 H1 is accepted and H0 is rejected. This means that the ability of the experimental group to recognize hijaiyah letters is superior to that of the control group. Based on this, it is proven that the index card match learning model through missing hijaiyah has a significant influence on the ability of children aged 5-6 years to recognize hijaiyah letters in Bontotiro sub-district